Education and Consumer Informatics - Boyer, C.; Section Editor for the IMIA Yearbook Section on Education and Consumer Informatics (Yearbook of Medical Informatics, 2010)
Objectives: To evaluate the extent to which the Internet is accessed for health information and perceived as useful to varying groups classified primarily according to age.Method: Synopsis of the articles on education and consumer health informatics selected for the IMIA Yearbook of Medical Informatics 2010.Results: A growing number of individuals are actively seeking health information through a varying selection of resources. The Internet is now seen as a major source of health information alongside with books and other means of paper-based literature. However, it is not clear how the Internet is perceived by varied groups such as those coming from differing age groups.Conclusion: The papers selected attempt to obtain a better understanding about how the public perceives and uses the Internet as an information gathering tool—especially for health information. The papers also explore into how the Internet is used by different groups of people. As all online health information is not of uniform quality, it is important to access and rely on quality medical information. This issue is also dealt with, where the popularity of Wikipedia is measured with the popularity of reliable web sources such as Medline Plus and NHS Direct.
Keywords: Quality online information; criteria; training; education; online information